Design and development of a slender dual-structure continuum robot for in-situ aeroengine repair - Wang, Mingfeng; Palmer, David; Dong, Xin; Alatorre, David; Axinte, Dragos A.; Norton, Andy (2018)
In-situ aeroengine maintenance works (e.g. inspection, repair) are highly beneficial as it can significantly reduce currently accepted maintenance cycle which is extensive and costly due to the need to remove engines from the wing of an aircraft. However, feeding in/out via inspection ports and performing a multi-axis movement of an end-effector in a very constrained environment such as aeroengine combustion chamber is a fairly challenging task. This paper presents the design and development of a highly slender (i.e., low diameterto-length ratio) dual-structure continuum robot with 16 degrees of freedom (DoFs) to provide the feeding motion needed to navigate into confined environments and then perform a required configuration shape for further repair operation. This continuum robot is a compact system and presents a set of innovative mechatronic solutions such as: (i) two-stage tendondriven structure with bevelled disk design to perform required configuration shape and to provide selective stiffness for the ability of taking high payloads; (ii) various compliant joints to enable different flexibility requirement in each stage; (iii) three commanding cables for each 2-DoF section to minimise the number of actuators with a precise actuation. To be able to achieve the desired configuration shape, a kinematic model has been established and the configuration-cable kinematics has been implemented. Finally, the continuum robot has been built and tested for performing the predefined configuration shape.